2019
DOI: 10.1079/hai.2019.0002
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Processes Involved in the Development of a High-Quality Relation with one’s Dog

Abstract: Background. Several studies have found an effect of pet ownership on human health and well-being. We propose that these benefits can only occur when the pet owner perceives the dog in a certain way: As having a human-like psychological functioning and experience of the world (anthropomorphism), and as part of one’s identity (assimilation). These perceptions are thought to support the development of a high-quality relationship with the dog that can lead to positive effects on health and well-being. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…A central test was whether the relationship of the two measures of anthropomorphization with the three outcomes was mediated by the perception of the pet's social role; the extent to which the pet was perceived in terms of being a child, a friend, a family member, and provider of love [17,26,27]. The correlational analyses showed that both measures of anthropomorphization were indeed significantly, albeit weakly, related to the perception of the social role of the pet (0.16 IDAQ and 0.38 COANT) and the correlations of the perception of the social role of the pet with the three outcomes measures were all significant and of substantial magnitude (0.43 to 0.65).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A central test was whether the relationship of the two measures of anthropomorphization with the three outcomes was mediated by the perception of the pet's social role; the extent to which the pet was perceived in terms of being a child, a friend, a family member, and provider of love [17,26,27]. The correlational analyses showed that both measures of anthropomorphization were indeed significantly, albeit weakly, related to the perception of the social role of the pet (0.16 IDAQ and 0.38 COANT) and the correlations of the perception of the social role of the pet with the three outcomes measures were all significant and of substantial magnitude (0.43 to 0.65).…”
Section: Discussionmentioning
confidence: 99%
“…Being a family member (instead of a mouser) was, for example, associated with a stronger attribution of friendliness and intelligence to cats by their owners [24] and when dog owners thought of their dogs as children, they rated them as more empathic [25]. These findings suggest that people form (human-like) perceptions of their pets' social role [17,26,27] that might influence their behavior towards the pet.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation